CHALLENGES FACING PUBLIC WORKS DEPARTMENTS IN CONSTRUCTION PROJECT DELIVERY WITHIN METROPOLITAN MUNICIPAL AND DISTRICT ASSEMBLIES IN GHANA - Kissi, E.; Mohammed, S. A.; Owusu-Diatuo, K. J. (UDS International Journal of Development, 2018)
There is growing concern over the successful implementation of projects in various Public Works Department (PWDs) at Metropolitan, Municipal and District Assemblies (MMDAs). In recent times MMDAs are challenged with the issues of poor project delivery rendering. This has led to a low confidence in public service administration in terms of construction projects delivery. The aim of this study was to appraise the challenges faced by the PWDs in project delivery. Based on relative importance index analysis the trend of the challenges were weather and other environmental challenges, unrealistic timelines for project delivery, influence of processes by political heads, inadequate logistics and inadequate human resource to carry out supervision among others. The implication is that Local Government Ministry should put in place measures for updating, assessing and improving the knowledge base on contract management of projects teams within MMDAs. Keywords: Public Works Departments (PWDs), Project Delivery, Metropolitan Municipal and District Assemblies (MMDAs), Projects